The discipline and effectiveness of the opposition groups in Parliament in the cases of interpellations during the governments of Toledo, Humala and García (2001-2013) - Vela, Estelí (2014)
This article discusses the use of the mechanism of parliamentary control of interpellation to ministers in the Peruvian case, with the objective of stablish which factors determine the effectives of opposition groups to approve the motions of interpellations they present during the post- Fujimori goverrnments of Alejandro Toledo, Alan García and Ollanta Humala (2001-2013). Taking into account the size, discipline and the number of motions presented, this research argues that the most effective parliamentary groups have high levels of discipline and present a reasonable number of motions, in relation to their capacity to approve them. The levels of discipline and effectiveness of each parliamentary group were calculate through the recompilation ofdata from 85 motions and 36 debates about the admission of the process.